Applying The Fe+3 Oxidizer As An Improvement In The Efficiency Of Uranium Extraction - et. al., Sharafutdinov U.Z, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Almost all industrial uranium deposits in the Republic of Uzbekistan are located in the Kyzylkum region. For the development of these deposits, the Navoi Mining and Metallurgical Combine (NMMC) was created, which is one of the world elite of uranium producers. The products manufactured by the plant provide a significant inflow of foreign currency to the Republic and therefore have significant national economic importance.